Functional roles of the birch BpRAV1 transcription factor in salt and osmotic stress response. (February 2022) - Hu, Ping; Zhang, Kaimin; Yang, Chuanping
Highlights: A novel RAV transcription factor BpRAV1 from B. platyphylla was functionally characterized. BpRAV1 encodes a nuclear protein, which can specifically bind to the known RAV1A element and a novel cis -acting element. BpRAV1 modulates salt and osmotic response through activation of anti-oxidative enzymes and genes. BpRAV1 is a promising candidate gene to employ in breeding abiotic stress-tolerant birch plants. Abstract: RAV (Related to ABI3/VP1) transcription factors play vital roles in regulating plant response to abiotic stresses; however, the regulatory mechanisms underlying stress response are still poorly understood for most of the RAV genes. In this study, a novel gene BpRAV1 was cloned from white birch ( Betula platyphylla ). BpRAV1 protein is localized in the nucleus and serves as a transcriptional activator. The expression of BpRAV1 was induced by salt and osmotic stress treatments. BpRAV1- overexpression birch seedlings exhibited dramatically less ROS accumulation and reduced cell death in response to salt and osmotic stresses. BpRAV1 can specifically bind to the known RAV1A element. In addition, a novel cis -acting element (termed RBS1) bound by BpRAV1 was identified by transcription factor (TF)- centered Y1H assay. BpRAV1 activated the RAV1A and RBS1 elements to induce the expression of SOD and POD genes, resulting in increased SOD and POD activities to enhance ROS scavenging ability, thus improving salt and osmotic stress tolerance. These results indicate that BpRAV1 is a positive regulator governing abiotic stress response.